2006
DOI: 10.1177/0363546506290402
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Reduce the Tensile Strength of Isolated Collagen Fascicles

Abstract: Corticosteroids may weaken specific regions of the injected tendon and leave it more prone to rupture. This weakening effect is manifested in the individual collagen fascicles that constitute the tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 43 publications
1
41
0
2
Order By: Relevance
“…The main finding of the present study was that individual rat‐tail tendon collagen fascicles had significantly lower yield stress and material stiffness (Young's modulus) 3 days after corticosteroid injection compared with collagen fascicles that were harvested from tails injected with 9% saline, while the strain properties of the fascicles remained unaffected. The present results confirm previous data obtained using an in vitro model (Haraldsson et al, 2006), while demonstrating a deleterious effect of corticosteroid injection on tendon collagen material properties using an in vivo model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main finding of the present study was that individual rat‐tail tendon collagen fascicles had significantly lower yield stress and material stiffness (Young's modulus) 3 days after corticosteroid injection compared with collagen fascicles that were harvested from tails injected with 9% saline, while the strain properties of the fascicles remained unaffected. The present results confirm previous data obtained using an in vitro model (Haraldsson et al, 2006), while demonstrating a deleterious effect of corticosteroid injection on tendon collagen material properties using an in vivo model.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it was also recently shown that incubation in corticosteroid solutions for 3 and 7 days markedly reduced the tensile strength of isolated collagen fascicles (Haraldsson et al, 2006). The purpose of the present study was to examine whether the biomechanical effects observed in the aforementioned in vitro study (Haraldsson et al, 2006) could be extended to an in vivo model of intratendinous corticosteroid injections on healthy rat‐tail tendon collagen fascicles. We hypothesized that the collagen fascicles receiving the corticosteroid injection would display reduced biomechanical properties compared with the controls.…”
mentioning
confidence: 92%
“…Some authors have hypothesized that any beneficial effects of corticosteroids in this condition are owed to other local steroid effects rather than suppression of inflammation, including lyses of tendon and peritendon adhesions or alteration of the function of pain generating nociceptor in the region [68]. Corticosteroid injections may have some benefit in the short term, but adverse effects were reported in up to 82% of corticosteroid trials [69]; these include tendon atrophy [69], tendon rupture [70], and decreased tendon strength [71, 72]. Corticosteroid injections could cause vasoconstriction through prostacyclin and adrenoceptors and inhibit nitric oxide synthase, which may be the source of adverse effects [20].…”
Section: Treatmentmentioning
confidence: 99%
“…For example, a randomized, controlled clinical trial of patients with chronic cuff tendinosis or partial cuff tear reported subacromial injection of betamethasone no more effective in improving the quality of life, Neer impingement sign, and range of motion than xylocaine alone at 2, 6, 12, and 24 weeks after injection [1]. A recent in vitro study attempted to characterize the direct effects of corticosteroids on the mechanical properties and collagen crosslink amount of isolated collagen fascicles [33]. Incubating rat tail collagen fascicles in either high or low concentration of methylprednisolone acetate for 3 or 7 days reduced tensile strength by approximately 45% to 66% compared with saline-treated controls.…”
Section: The Role Of Corticosteroids On Tendon-bone Healingmentioning
confidence: 99%